2019
DOI: 10.1186/s12866-019-1422-x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, molecular epidemiology, and antimicrobial resistance of methicillin-resistant Staphylococcus aureus from swine in southern Italy

Abstract: Background Colonization by livestock-associated MRSA (LA-MRSA) has increasingly been reported in the swine population worldwide. The aim of this study was to assess the prevalence of MRSA nasal carriage in healthy pigs, including the black ( Calabrese ) breed, from farms in the Calabria Region (Southern Italy). Between January and March 2018, a total of 475 healthy pigs reared in 32 farms were sampled by nasal swabbing. MRSA isolates were characterized by s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
51
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(62 citation statements)
references
References 68 publications
10
51
1
Order By: Relevance
“…MRSA is probably the best example of a prevalent and important multidrug-resistant bacterium that has successfully transitioned from an almost exclusively nosocomial setting to being widespread in the community [29]. All obtained MRSA isolates in this study were multidrug-resistant strains (exhibiting resistance to 3-5 antibiotic categories), a result which was in accordance with that reported in healthy bovines in Belgium [12] and healthy pigs in Southern Italy [13].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…MRSA is probably the best example of a prevalent and important multidrug-resistant bacterium that has successfully transitioned from an almost exclusively nosocomial setting to being widespread in the community [29]. All obtained MRSA isolates in this study were multidrug-resistant strains (exhibiting resistance to 3-5 antibiotic categories), a result which was in accordance with that reported in healthy bovines in Belgium [12] and healthy pigs in Southern Italy [13].…”
Section: Discussionsupporting
confidence: 88%
“…After being well established in the health-care setting, MRSA found its way towards the community and now community-acquired MRSA has a mounting public health burden [11]. Given the serious threat of zoonotic MRSA transmission, the subsequent detection of multidrug-resistant MRSA among animals was of major concern [12,13]. Therefore, the current study was conducted in order to investigate the occurrence of multidrug-resistant MRSA among apparently healthy farm animals to shed more light on the potential role of these animals as a reservoir for multidrug-resistant MRSA.…”
Section: Introductionmentioning
confidence: 99%
“…Most of isolates, particularly obtained from pigs and chicken, in this study, were high resistance and multi-drug resistant. The high prevalence of resistance to antimicrobials in our study was similar to that reported in previous studies [1,29,33,35]. Antimicrobial agents are often used for the prevention and treatment of infectious diseases and growing promotion of food producing animals in intensive production.…”
Section: Discussionsupporting
confidence: 91%
“…Nevertheless, the long-term use of antibiotics in animal breeding can accelerate the emergence of antibiotic-resistant bacteria (ARB), including Staphylococcus aureus, which can cause trauma infection, abscess, cellulitis, mastitis, endometritis, arthritis, septicemia, and sepsis in animals (Fluit, 2012;Foster, 2012;Dan et al, 2019). It has been found that S. aureus is resistant to tetracycline, methicillin, erythromycin, clindamycin, ciprofloxacin, and vancomycin (Hiramatsu, 2001;Lai et al, 2018;Pirolo et al, 2019). The interactions among animals, humans, and the environment have also strengthened the spreading of ARB (Cheng et al, 2013;Laxminarayan et al, 2013;Maertens et al, 2019).…”
Section: Introductionmentioning
confidence: 99%